Within- and cross-language semantic effects on oral word translation with a word flanker paradigm - Yong Zhang; Ziqian Yu; Jieyang Yu; Qianyu Ye; Yan Jing Wu (Language and Cognition)
When a word is being translated, its immediately adjacent lexical items may impact the translation of the target word. However, the impact of adjacent lexical items on the oral translation of a target word situated in central vision remains unexplored. This behavioral study used a bilingual version of the flanker paradigm to examine the impact of within- and cross-language semantic effects on oral word translation. Unbalanced bilinguals were presented with a central target word that was flanked by two flanking words on either side. The target-flanker relations were manipulated as a function of semantic relatedness (identical, related and unrelated) and language congruency (congruent and incongruent). The task was to orally translate the target word from L1 to L2 (forward translation) in one session and from L2 to L1 (backward translation) in the other while ignoring the flanker words. Results showed faster responses for forward compared to backward translation. Moreover, in within-language (congruent) but not in cross-language (incongruent) contexts, semantic priming effects were observed in both directions of translation, with the effects being larger for backward than forward translation. Additionally, substantial cross-language semantic repetition priming effects were obtained. The findings are discussed within the framework of a two-process account for oral word translation.